What's new in obstetric anesthesia in 2017?. (May 2019) - Habib, A.S.
Highlights: This is a review of 2017 literature relevant to obstetric anesthesiologists. It focuses on maternal mortality and cardiac arrest during pregnancy. It includes relevant publications related to cesarean delivery and labor analgesia. Abstract: The Gerard W. Ostheimer lecture is delivered every year at the annual meeting of the Society for Obstetric Anesthesia and Perinatology. The lecture aims to provide the anesthesiologist who provides obstetric anesthesia care with a review of the most relevant articles that were published in the preceding calendar year. This article highlights the literature published in 2017 related to maternal mortality, maternal cardiac arrest, cesarean delivery and labor analgesia.